Secondary studies teaching in some state secondary schools of England its implication to social studies teaching in Philippine public secondary schools - Cruz, Leonardo D. de la 1931- (s.n.], 1966)
This study examined the social studies program in some of the state secondary schools of England and its implications on social studies teaching in Philippine public secondary schools. This is centered on the objectives, organization of courses, physical and instructional materials, methods of teaching, and methods of assessment of the program.